Akar Orientasi Keagamaan dalam Pemikiran Pendidikan Islam - Hery Noer Aly (At-Ta'lim : Media Informasi Pendidikan Islam, 2020)
Abstract: The Root of Religious Orientation in Islamic Education Thought. This study is aimed at exploring the roots of religious orientation in Islamic education thought. The method used in this study is literature study; by exploring the similarities and differences in the thoughts of leading Muslim education experts, especially those listed in the book of Ihya Ulûm ad-Dîn and Ayyuhal Walad by al-Gazâli & Adâb al-Muta 'allimîn by Nasîr ad-Dîn aṭ-Ṭûsi. The result reveals that the principles of Islamic education that must be adhered to by educators must lead to the concept of religiosity, which is to seek the divine wisdom of Allah. Education is a moral responsibility and also a responsibility to Allah SWT. Hence, it emerges two sides of thought, namely the conservatives who underestimate worldly affairs and the modern side who are too concerned with the affairs of the world. The underlying causes of the two thoughts were born thinkers such as Ibn Sahnun, al-Qabisi (324-403 H), Ibn Miskawaih (d. 421 H), al-Gazali (450-505 H), at-Tusi (597-672 H) ), Ibn Jama'ah (639-733 H), Ibn Khaldun (732-808 H), and Ibn Hajar al-Haitami in Egypt (909-974 H). In the field, they have a different experiences in accordance with developing scientific studies, but they remain in one connecting line, namely religious orientation. Abstract: Akar Orientasi Keagamaan dalam Pemikiran Pendidikan Islam. Kajian ini bertujuan untuk mengeksplorasi akar orientasi keagamaan dalam pemikiran pendidikan Islam. Metode yang digunakan dalam penelitian ini adalah studi pustaka, yakni dengan mengksplorasi kajian terhadap persamaan dan perbedaan dalam beragam pemikiran pakar pendidikan muslim terkemuka, terutama yang tercantum dalam kitab Ihya Ulûm ad-Dîn, dan Ayyuhal Walad karya al-Gazâli & Adâb al-Muta’allimîn karya Nasîr ad-Dîn aṭ-Ṭûsi. Hasil penelusuran mengungkapkan bahwa prinsip-prinsip pendidikan Islam yang harus dipegang oleh para pendidik harus bermuara pada konsep religiusitas, yakni mencari kiridaan Allah Swt. Pendidikan merupakan tanggung jawab moral dan juga tanggung jawab kepada Allah Swt. Dari sini muncullah dua sisi pemikiran, yakni kaum konservatif yang menganggap rendah urusan dunia dan kaum modern yang tertalu mengedepankan urusan dunia. Benang merah dari dua pemikiran itu lahirlah para pemikir seperti Ibn Sahnun, al-Qabisi (324-403 H), Ibn Miskawaih (w. 421 H), al-Gazali (450-505 H), at-Tusi (597-672 H), Ibn Jama’ah (639-733 H), Ibn Khaldun (732-808 H), dan Ibn Hajar al-Haitami di Mesir (909-974 H). Di lapangan, mereka mengalami perbedaan sesuai dengan kajian ilmu pengetahuan yang berkembang, tetapi mereka tetap berada dalam satu benang merah, yaitu orientasi keagamaan.